Sexual Conflict over the Maintenance of Sex: Effects of Sexually Antagonistic Coevolution for Reproductive Isolation of Parthenogenesis - Kawatsu, Kazutaka (PLOS ONE, 2013)
Sexual reproduction involves many costs. Therefore, females acquiring a capacity for parthenogenetic (or asexual) reproduction will gain a reproductive advantage over obligately sexual females. In contrast, for males, any trait coercing parthenogens into sexual reproduction (male coercion) increases their fitness and should be under positive selection because parthenogenesis deprives them of their genetic contribution to future generations. Surprisingly, although such sexual conflict is a possible outcome whenever reproductive isolation is incomplete between parthenogens and the sexual ancestors, it has not been given much attention in the studies of the maintenance of sex. Using two mathematical models, I show here that the evolution of male coercion substantially favours the maintenance of sex even though a female barrier against the coercion can evolve. First, the model based on adaptive-dynamics theory demonstrates that the resultant antagonistic coevolution between male coercion and a female barrier fundamentally ends in either the prevalence of sex or the co-occurrence of two reproductive modes. This is because the coevolution between the two traits additionally involves sex-ratio selection, that is, an increase in parthenogenetic reproduction leads to a female-biased population sex ratio, which will enhance reproductive success of more coercive males and directly promotes the evolution of the coercion among males. Therefore, as shown by the individual-based model, the establishment of obligate parthenogenesis in the population requires the simultaneous evolution of strong reproductive isolation between males and parthenogens. These findings should shed light on the interspecific diversity of reproductive modes as well as help to explain the prevalence of sexual reproduction.